Agricultural-Mechanization Education Program Development in Albania - Harrison, John D. (Journal of Agricultural Systems, Technology, and Management, 2001)
Education and training programs developed in Albania address the need for knowledge and skills associated with modern agricultural systems. Agricultural education methods, program development, and management are increasingly important as Albania joins the developing countries of Eastern Europe. The objective of these programs is the education of instructors and teachers. The target group comprises professional agriculturists at university and secondary/technical schools. These professionals, with the support of the Ministry of Education and the Ministry of Agriculture and Food of the Republic of Albania, are linked in an effort known as the Alliance for Vocational Agricultural Training in the Albanian Region (AVATAR).